THE EFFICIENCY OF FUNCTIONAL TRAINING ON REPETITIVE STRENGTH IN WOMEN - Nataša Nikić; Dejan Milenković (Sport Scientific And Practical Aspects, 2025)
The aim of this study was to determine the efficiency of functional training on repetitive strength of 30 female trainees (age: 28.6 ± 6.71) in the premises of aerobic studio "NIA" from Niš. There were two groups, one of which was performing 3-months experimental program of functional training, while the other group was the control one without any organized physical activity. Repetitive strength was estimated with Eurofit 30 seconds sit up test, straight leg abdominal strength test, squat test, single leg (left) squat test, single leg (right) squat test, chair push up test, push up test. In addition to analyzing the basic statistical parameters (mean and standard deviation) Student’s t-test and analysis of covariance were used for calculating intragroup and intergroup relations and the assessment of working effect. Results showed that functional training had a positive effect on repetitive strength of female trainees after three months (p < 0. 01).